Antihyperglycemic studies with boiled and non-boiled Vigna mungo seeds - Shakila Jahan Mou, Md Rasel Ahmed, Shahnaz Rahman, ABM Anwarul Bashar, Erena Islam, Mohammed Rahmatullah (Journal of Applied Pharmaceutical Science, 2015)
Vigna mungo is a common leguminous crop cultivated in Bangladesh for its edible seeds, which are consumed following boiling or cooking. Since many lentil plants are known to have antihyperglycemic activity, it was of interest to determine the antihyperglycemic potential of seeds of V. mungo both in its boiled and non-boiled form. In oral glucose tolerance tests conducted in glucose-loaded Swiss albino mice, crude methanol extract of non-boiled seeds reduced blood glucose levels by 29.1, 36.5, 42.6, and 48.9%, respectively, at doses of 50, 100, 200, and 400 mg per kg body weight. At the afore-mentioned four doses, the percent reductions in blood glucose levels were, respectively, 24.1, 35.1, 39.4, and 46.5% with crude methanol extract of boiled seeds. Glibenclamide, a standard antihyperglycemic drug was observed to reduce blood glucose levels by 48.2%, when administered at a dose of 10 mg per kg. Thus the extracts of both non-boiled and boiled seeds demonstrated good antihyperglycemic potential comparable to glibenclamide and can be used as a readily available alternative to alleviate high blood glucose levels in diabetic patients.
Keywords: Vigna mungo, antihyperglycemic, Fabaceae, legume.